Census as a Source of Secondary Data - McEachern, Leslie Carlton (My University, 1974)
This thesis was an attempt at considering census data as a viable source of data for secondary social research. Through the use of hypothetical research problems, the data was examined for possible errors. Several were found but upon further examination, they were found to be insignificant in the distirtion of analysis of data. The findings of the hypothetical research problem, the construction of socio-economic scores for the Provinces of Ontario and Quebec, were as follows; no significant differences were found to exist between major occupational categories for Ontario and Quebec. There were some sizeable differences between some single occupations between the two provinces, but on the aggregate, these made little difference for comparative analysis. In sum, we found the census to be a usefull source of data for secondary analysis.
Keywords: Sociology; Sociology